Atazanavir increases the plasma concentrations of 1200 mg raltegravir dose. (4th November 2016) - Krishna, Rajesh; East, Lilly; Larson, Patrick; Valiathan, Chandni; Deschamps, Kathleen; Luk, Julie Ann; Bethel‐Brown, Crystal; Manthos, Helen; Brejda, John; Gartner, Michael
Abstract: Raltegravir is a human immunodeficiency virus (HIV)‐1 integrase strand transfer inhibitor currently marketed at a dose of 400 mg twice‐daily (b.i.d.). Raltegravir 1200 mg once‐daily (q.d.) (investigational q.d. formulation of 2 × 600 mg tablets; q.d. RAL) was found to be generally well tolerated and non‐inferior to the marketed 400 mg b.i.d. dose at 48 weeks in a phase 3 trial. Since raltegravir is eliminated mainly by metabolism via a uridine diphosphate glucuronosyltransferase (UGT) 1A1‐mediated glucuronidation pathway, co‐administration of UGT1A1 inhibitors may increase the plasma levels of q.d. RAL. To assess this potential, the drug interaction of 1200 mg raltegravir using atazanavir, a known UGT1A1 inhibitor, was studied. An open‐label, randomized, 2‐period, fixed‐sequence phase 1 study was performed in adult healthy male and female (non‐childbearing potential) subjects ≥ 19 and ≤ 55 years of age, with a body mass index (BMI) ≥ 18.5 and ≤ 32.0 kg/m 2 . Subjects ( n = 14) received a single oral dose of 1200 mg raltegravir in period 1. After a washout period of at least 7 days, the subjects received oral doses of 400 mg atazanavir q.d. for 9 consecutive days, with a single oral dose of 1200 mg raltegravir co‐administered on day 7 of period 2. Serial blood samples were collected for 72 h following raltegravir dosing and analysed using a validated bioanalytical method to quantify raltegravir plasma concentrations. Co‐administration with atazanavir yielded GMRs (90% CIs) for raltegravir AUC 0‐∞, C max and C 24 of 1.67 (1.34, 2.10), 1.16 (1.01, 1.33) and 1.26 (1.08, 1.46), respectively. There was no effect of raltegravir on serum total bilirubin. In contrast, atazanavir increased the mean bilirubin by up to 200%, an effect that was preserved in the atazanavir/raltegravir treatment group. Administration of single q.d. RAL alone and co‐administered with multiple oral doses of atazanavir were generally well tolerated in healthy subjects. The results show that atazanavir increased the PK exposure of raltegravir; therefore, co‐administration of atazanavir with raltegravir q.d. is not recommended. Copyright © 2016 John Wiley & Sons, Ltd.